Maritime Legal Politics in Preventing Marine Pollution Due to Ship Traffic - Ndori, Akhmad (UNISSULA, 2024)
The high volume of global ship traffic, including in Indonesia, poses significant risks to the marine environment due to pollution from oil spills, liquid waste, and plastic waste. This study aims to analyze Indonesia's maritime legal policies in preventing marine pollution, with a focus on the challenges in enforcing international conventions. This study uses a doctrinal approach method. Indonesia's maritime legal policy in preventing marine pollution due to ship traffic has developed, driven by international regulations such as the MARPOL Convention and UNCLOS. National law about Environmental Protection and Management, play an important role in regulating and enforcing pollution prevention policies. However, the implementation of the law still faces various challenges, such as weak law enforcement, less than optimal coordination between institutions, and limited technology and supporting facilities. Efforts to strengthen law enforcement and the application of international standards are needed to protect the marine environment from pollution due to ship activities.